An alternative to the "unwritten alliance" : the policy of a persuasive approximation between Brazil and the United States (1889-1906) - Bodart, Olivier Nicolas Ronald François (2018)
This work aims at presenting an alternative version to the unwritten alliance that commonly describes the U.S. and Brazil relations at the beginning of the 20th century when they became closer and more intense. By unpacking the foreign policy strategies of each party and the perception of power towards each other, it appeared that Washington and Rio de Janeiro shared a perception of international changes as far as hemispherical matters. This converged into a persuasive approximation that mainly served Brazilian interests to contain the Argentine republic’s ambitions and divergent influences; without nonetheless the need to officialize the specific relation.